Stability of soluble adhesion molecules, selectins, and C-reactive protein at various temperatures: implications for epidemiological and large-scale clinical studies. - Hartweg, J; Gunter, M; Perera, R; Farmer, A; Cull, C; Schalkwijk, C; Kok, A; Twaalfhoven, H; Holman, R; Neil, A (2007)
BACKGROUND: We assessed the impact of sample storage conditions on soluble vascular cell adhesion molecules (sVCAM), soluble intracellular adhesion molecules (sICAM-1), soluble (s)E-selectin, C-reactive protein (CRP), and sP-selectin. METHODS: Markers were measured by ELISA in venous blood from 10 healthy volunteers on aliquots stored as plasma or whole blood at 4, 21, or 30 degrees C for 1-5 days and after 1-5 freeze-thaw cycles. We compared results on these samples to results for samples processed immediately and stored at -80 degrees C. Statistical models assessed time-related effects and effects of postprocessing conditions. RESULTS: Using an upper limit of 10% variation from baseline with P >0.05, we found that stability duration in plasma was 5 days for sVCAM-1 and sICAM-1 and at least 2 days for sE-selectin at 4, 21, and 30 degrees C and 5 days for CRP at 4 and 21 degrees C and 1 day at 30 degrees C. Stability duration in whole blood was 5 days for sVCAM-1 and sICAM-1 and at least 2 days for sE-selectin at 4, 21, and 30 degrees C and 5 days for CRP at 4 and 21 degrees C and 2 days at 30 degrees C. sP-selectin was not stable in plasma or whole blood. sICAM-1, sVCAM-1, CRP, and sE-selectin were stable after 5 freeze-thaw cycles. CONCLUSIONS: sVCAM-1, sICAM-1, and CRP are stable in plasma or whole blood at 4 and 21 degrees C for at least 3 days and sE-selectin for 2 days. sP-selectin is not stable and therefore requires immediate assay.